Studies on melobesioideae of Japan. - Masaki, Tomitaro (Hokkaido, Japan Hokkaido University Press, 1968)
Reprinted from Memoirs of the Faculty of Fisheries, Hokkaido University, vol. 16, No. 1/2, pp.1-80 Dec 1968
Keywords: Melobesioideae